Move <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> by <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> .

Combine <math><mstyle displaystyle="true"><msup><mrow><mi>b</mi></mrow><mrow><mn>2</mn></mrow></msup></mstyle></math> and <math><mstyle displaystyle="true"><mfrac><mrow><mn>3</mn></mrow><mrow><mn>7</mn></mrow></mfrac></mstyle></math> .

Combine.

Multiply <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mn>7</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>7</mn></mstyle></math> .

Move <math><mstyle displaystyle="true"><mn>12</mn></mstyle></math> to the left of <math><mstyle displaystyle="true"><msup><mrow><mi>b</mi></mrow><mrow><mn>2</mn></mrow></msup></mstyle></math> .

Do you know how to Simplify the Radical Expression (b3/7)(b4/7)? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.